2007
DOI: 10.1136/gut.2006.114066
|View full text |Cite
|
Sign up to set email alerts
|

Temporal relationship between hepatitis B virus enhancer II/basal core promoter sequence variation and risk of hepatocellular carcinoma

Abstract: HCC risk is associated with sequence variation in the EnhII/BCP regions of HBV, and persistence of at-risk sequence variants is critical for HCC development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 35 publications
5
95
1
Order By: Relevance
“…To our knowledge, the current case-control study is the first to reveal the association between HBV mutations and the development of HCC among Thai patients. In this study, we found that double A1762T/G1764A mutations were an independent risk factor for the development of HCC, which was consistent with recent casecontrol studies conducted in China, Taiwan, and Korea [7,12,20,21]. Also, the magnitude of the OR of HCC associated with the presence of the BCP double mutants in this study was approximately 3 to 4-fold, which was similar with reports of other studies.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, the current case-control study is the first to reveal the association between HBV mutations and the development of HCC among Thai patients. In this study, we found that double A1762T/G1764A mutations were an independent risk factor for the development of HCC, which was consistent with recent casecontrol studies conducted in China, Taiwan, and Korea [7,12,20,21]. Also, the magnitude of the OR of HCC associated with the presence of the BCP double mutants in this study was approximately 3 to 4-fold, which was similar with reports of other studies.…”
Section: Discussionsupporting
confidence: 92%
“…26 By characterizing the HBV genome sequences derived from patients' serum, several studies have illustrated that various virological factors are closely associated with hepatocarcinogenesis, including serum HBV-DNA concentration, genotype, and the presence of a basal core promoter mutation. 27 Furthermore, by performing cell-based and animalbased experiments, several viral proteins have been shown to be implicated in the oncogenesis of liver cancer, including X proteins, large surface proteins, and pre-S deletion mutants. 23,28,29 Despite convincing evidence provided by these studies, the link between HBV and carcinogenesis has not been carefully investigated by examining the prognostic value of these virological factors in a postoperative model.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the baseline HBV mutations in combination are able to predict the occurrence of HCC in CHB patients [33] . Several longitudinal studies carried in China have also demonstrated that baseline A1762T/G1764A mutation increases the risk of HCC in chronic HBV carriers or CHB patients [34][35][36][37] . Among the HCC-risk HBV mutations, the A1762T/G1764A is usually detected in the early stage in young adolescents, while other mutations including T1753V, C1653T, G1899A, and preS deletion appear only at the late stage of chronic HBV infection [12,38] .…”
Section: "Dead-end" Evolution Of Hbvmentioning
confidence: 98%